<< Chapter < Page Chapter >> Page >
In this section, you will:
  • Apply the Binomial Theorem.

A polynomial with two terms is called a binomial. We have already learned to multiply binomials and to raise binomials to powers, but raising a binomial to a high power can be tedious and time-consuming. In this section, we will discuss a shortcut that will allow us to find ( x + y ) n without multiplying the binomial by itself n times.

Identifying binomial coefficients

In Counting Principles , we studied combinations . In the shortcut to finding ( x + y ) n , we will need to use combinations to find the coefficients that will appear in the expansion of the binomial. In this case, we use the notation ( n r ) instead of C ( n , r ) , but it can be calculated in the same way. So

( n r ) = C ( n , r ) = n ! r ! ( n r ) !

The combination ( n r ) is called a binomial coefficient . An example of a binomial coefficient is ( 5 2 ) = C ( 5 , 2 ) = 10.

Binomial coefficients

If n and r are integers greater than or equal to 0 with n r , then the binomial coefficient    is

( n r ) = C ( n , r ) = n ! r ! ( n r ) !

Is a binomial coefficient always a whole number?

Yes. Just as the number of combinations must always be a whole number, a binomial coefficient will always be a whole number.

Finding binomial coefficients

Find each binomial coefficient.

  1. ( 5 3 )
  2. ( 9 2 )
  3. ( 9 7 )

Use the formula to calculate each binomial coefficient. You can also use the n C r function on your calculator.

( n r ) = C ( n , r ) = n ! r ! ( n r ) !
  1. ( 5 3 ) = 5 ! 3 ! ( 5 3 ) ! = 5 4 3 ! 3 ! 2 ! = 10
  2. ( 9 2 ) = 9 ! 2 ! ( 9 2 ) ! = 9 8 7 ! 2 ! 7 ! = 36
  3. ( 9 7 ) = 9 ! 7 ! ( 9 7 ) ! = 9 8 7 ! 7 ! 2 ! = 36
Got questions? Get instant answers now!
Got questions? Get instant answers now!

Find each binomial coefficient.

  1. ( 7 3 )
  2. ( 11 4 )

  1. 35
  2. 330

Got questions? Get instant answers now!

Using the binomial theorem

When we expand ( x + y ) n by multiplying, the result is called a binomial expansion    , and it includes binomial coefficients. If we wanted to expand ( x + y ) 52 , we might multiply ( x + y ) by itself fifty-two times. This could take hours! If we examine some simple binomial expansions, we can find patterns that will lead us to a shortcut for finding more complicated binomial expansions.

( x + y ) 2 = x 2 + 2 x y + y 2 ( x + y ) 3 = x 3 + 3 x 2 y + 3 x y 2 + y 3 ( x + y ) 4 = x 4 + 4 x 3 y + 6 x 2 y 2 + 4 x y 3 + y 4

First, let’s examine the exponents. With each successive term, the exponent for x decreases and the exponent for y increases. The sum of the two exponents is n for each term.

Next, let’s examine the coefficients. Notice that the coefficients increase and then decrease in a symmetrical pattern. The coefficients follow a pattern:

( n 0 ) , ( n 1 ) , ( n 2 ) , ... , ( n n ) .

These patterns lead us to the Binomial Theorem , which can be used to expand any binomial.

( x + y ) n = k = 0 n ( n k ) x n k y k = x n + ( n 1 ) x n 1 y + ( n 2 ) x n 2 y 2 + ... + ( n n 1 ) x y n 1 + y n

Another way to see the coefficients is to examine the expansion of a binomial in general form, x + y , to successive powers 1, 2, 3, and 4.

( x + y ) 1 = x + y ( x + y ) 2 = x 2 + 2 x y + y 2 ( x + y ) 3 = x 3 + 3 x 2 y + 3 x y 2 + y 3 ( x + y ) 4 = x 4 + 4 x 3 y + 6 x 2 y 2 + 4 x y 3 + y 4

Can you guess the next expansion for the binomial ( x + y ) 5 ?

Graph of the function f_2.

See [link] , which illustrates the following:

  • There are n + 1 terms in the expansion of ( x + y ) n .
  • The degree (or sum of the exponents) for each term is n .
  • The powers on x begin with n and decrease to 0.
  • The powers on y begin with 0 and increase to n .
  • The coefficients are symmetric.

To determine the expansion on ( x + y ) 5 , we see n = 5 , thus, there will be 5+1 = 6 terms. Each term has a combined degree of 5. In descending order for powers of x , the pattern is as follows:

Questions & Answers

Cos45/sec30+cosec30=
dinesh Reply
Cos 45 = 1/ √ 2 sec 30 = 2/√3 cosec 30 = 2. =1/√2 / 2/√3+2 =1/√2/2+2√3/√3 =1/√2*√3/2+2√3 =√3/√2(2+2√3) =√3/2√2+2√6 --------- (1) =√3 (2√6-2√2)/((2√6)+2√2))(2√6-2√2) =2√3(√6-√2)/(2√6)²-(2√2)² =2√3(√6-√2)/24-8 =2√3(√6-√2)/16 =√18-√16/8 =3√2-√6/8 ----------(2)
exercise 1.2 solution b....isnt it lacking
Miiro Reply
I dnt get dis work well
john Reply
what is one-to-one function
Iwori Reply
what is the procedure in solving quadratic equetion at least 6?
Qhadz Reply
Almighty formula or by factorization...or by graphical analysis
Damian
I need to learn this trigonometry from A level.. can anyone help here?
wisdom Reply
yes am hia
Miiro
tanh2x =2tanhx/1+tanh^2x
Gautam Reply
cos(a+b)+cos(a-b)/sin(a+b)-sin(a-b)=cotb ... pls some one should help me with this..thanks in anticipation
favour Reply
f(x)=x/x+2 given g(x)=1+2x/1-x show that gf(x)=1+2x/3
Ken Reply
proof
AUSTINE
sebd me some questions about anything ill solve for yall
Manifoldee Reply
cos(a+b)+cos(a-b)/sin(a+b)-sin(a-b)= cotb
favour
how to solve x²=2x+8 factorization?
Kristof Reply
x=2x+8 x-2x=2x+8-2x x-2x=8 -x=8 -x/-1=8/-1 x=-8 prove: if x=-8 -8=2(-8)+8 -8=-16+8 -8=-8 (PROVEN)
Manifoldee
x=2x+8
Manifoldee
×=2x-8 minus both sides by 2x
Manifoldee
so, x-2x=2x+8-2x
Manifoldee
then cancel out 2x and -2x, cuz 2x-2x is obviously zero
Manifoldee
so it would be like this: x-2x=8
Manifoldee
then we all know that beside the variable is a number (1): (1)x-2x=8
Manifoldee
so we will going to minus that 1-2=-1
Manifoldee
so it would be -x=8
Manifoldee
so next step is to cancel out negative number beside x so we get positive x
Manifoldee
so by doing it you need to divide both side by -1 so it would be like this: (-1x/-1)=(8/-1)
Manifoldee
so -1/-1=1
Manifoldee
so x=-8
Manifoldee
SO THE ANSWER IS X=-8
Manifoldee
so we should prove it
Manifoldee
x=2x+8 x-2x=8 -x=8 x=-8 by mantu from India
mantu
lol i just saw its x²
Manifoldee
x²=2x-8 x²-2x=8 -x²=8 x²=-8 square root(x²)=square root(-8) x=sq. root(-8)
Manifoldee
I mean x²=2x+8 by factorization method
Kristof
I think x=-2 or x=4
Kristof
x= 2x+8 ×=8-2x - 2x + x = 8 - x = 8 both sides divided - 1 -×/-1 = 8/-1 × = - 8 //// from somalia
Mohamed
i am in
Cliff
1KI POWER 1/3 PLEASE SOLUTIONS
Prashant Reply
hii
Amit
how are you
Dorbor
well
Biswajit
can u tell me concepts
Gaurav
Find the possible value of 8.5 using moivre's theorem
Reuben Reply
which of these functions is not uniformly cintinuous on (0, 1)? sinx
Pooja Reply
helo
Akash
hlo
Akash
Hello
Hudheifa
which of these functions is not uniformly continuous on 0,1
Basant Reply
Practice Key Terms 3

Get the best Algebra and trigonometry course in your pocket!





Source:  OpenStax, Algebra and trigonometry. OpenStax CNX. Nov 14, 2016 Download for free at https://legacy.cnx.org/content/col11758/1.6
Google Play and the Google Play logo are trademarks of Google Inc.

Notification Switch

Would you like to follow the 'Algebra and trigonometry' conversation and receive update notifications?

Ask